Closure - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Scope of JIFAM PaperJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited to the following.- I & F Function- I & F Demand - Supply- I & F User Behavior- I & F Evaluation- I & F Policy- I & F Preliminary Idea- I & F Planning- I & F Design- I & F Construction- I & F Administration Aspects- I & F Technical Certification- I & F Information System- I & F Operation System- I & F Maintenance System- I & F Disposal- I & F Economics & Financial Aspect- I & F Spatial & Environmental Aspect- I & F Sustainability Aspects- I & F Strategic Aspect- Decision Making for I&FAM- Statistics for I&FAM- Mathematics for I&FAM- Operation Research for I&FAM- I & F Managing Organisation Aspect Paper Writing RegulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Paper is regulated by general stipulation as follows.- Papers must be a real work of the author.- Papers have never been published in other media.- Papers must contain discussion about Infrastructure & Facility Asset Management.- Papers must contain a new discussion, judging based on the discussion that has been published in previous JIFAM & JMAIF.- The paper must have a minimum of 8 references, 5 of them should be of recent primary references not older than 10 years.- Paper lengths are limited in 8-16 pages.- Typed in Microsoft Word- The submitted paper must be furnished with Grammarly Report as a result of the English check. - The submitted paper must be furnished with a Statement of No PlagiarismPaper and Statement Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifam